2022-RA-1336-ESGO Differences in epidemiology, clinical features and prognosis of EOC in arab women as compared with jewish women in Northern Israel. (20th October 2022) - Shachar, Inbar Ben; Plaschkes, Roni; Zidan, Jamal; Atlas, Ilan
Abstract : Introduction/Background: Epithelial ovarian cancer (EOC) is the most fatal gynecological cancer, affecting various ethnic groups differently. We compared between women from Israel's two major ethnic groups, Arabs and Jews, in order to determine whether significant differences in EOC characteristics existed. Methodology: The data consist of records of 122 women (24 Arabs and 98 Jews) with EOC who were treated in northern Israel between 2005 and 2017 and include the following: age at diagnosis, disease stage, histological type, histological grade, BRCA mutations, and prognosis. Results: Arab patients were diagnosed at a younger age compared with Jewish patients (60.0 years vs. 65.5 years, respectively; p = 0.050). Stage III-IV disease was found among 78.3% in Arabs and 79.1% in Jews (p = 0.928). Serous tumors were most common in both groups (75% of Arabs and 74.1% of Jews; p = 0.649). Of only four (16.6%) Arab women who were tested for BRCA mutations, two were found positive, while of 47 (47.9%) Jewish women who were tested, 23.4% were found with a mutation. Overall survival was similar in the two groups (5.8 years in Arabs vs. 5.9 years in Jews), but Arab patients died at a younger age compared with Jewish patients (65.9 years vs. 71.4 years, respectively; p = 0.089). Conclusion: The only significant difference observed was the younger age of diagnosis among the Arab patients. Only a small percentage of the Arab population underwent genetic screening during the study period, but new health ministry regulations will expand screening to all populations.